Potensi Stabilizer Alami Pati Uwi dalam Meningkatkan Kualitas Set Yogurt Susu Kambing Selama Masa Simpan - N A Usman; N Riffiandi (Politeknik Negeri Lampung, 2023)
Processing goat's milk into yoghurt products can reduce the distinctive aroma of 'prengus' by adding a starter that will break down lactose into lactic acid and switch the milk smell into a distinctive odour of yoghurt. It will also increase the consumption of goat's milk with higher nutritional value and extend the shelf life. This study aims to determine the potential of the natural stabilizer of uwi starch in improving the quality of set yoghurt goat's milk during its shelf-life. This study was conducted in experimental used CRD with four treatments (P1: 0-day storage, P2: 2 days storage, P3: 4 days storage, P4: 6 days storage) and five replications. Analysis of variance used to determine the potential of the natural stabilizer of uwi starch on total lactic acid bacteria, viscosity, and water content set yoghurt goat's milk. And then, Honestly Significant Difference was used to know the difference between the treatments. The results showed that the treatment adding a natural stabilizer of uwi starch was significantly different (P<0.05) in total lactic acid bacteria during storage and had no significant effect (P>0.05) on viscosity and water content during storage